The roles and involvement of global health partners in the health workforce: an exploratory analysis - Andrea Nove; Onyema Ajuebor; Khassoum Diallo; James Campbell; Giorgio Cometto (BMC, 2023)
Abstract Development partners and global health initiatives are important actors in financing health systems in many countries. Despite the importance of the health workforce to the attainment of global health targets, the contribution of global health initiatives to health workforce strengthening is unclear. A 2020 milestone in the Global Strategy on Human Resources for Health is that "all bilateral and multilateral agencies have participated in efforts to strengthen health workforce assessments and information exchange in countries." This milestone exists to encourage strategic investments in the health workforce that are evidence-based and incorporate a health labour market approach as an indication of policy comprehensiveness. To assess progress against this milestone, we reviewed the activities of 23 organizations (11 multilaterals and 12 bilaterals) which provide financial and technical assistance to countries for human resources for health, by mapping grey and peer-reviewed literature published between 2016 and 2021. The Global Strategy states that health workforce assessment involves a "deliberate strategy and accountability mechanisms on how specific programming contributes to health workforce capacity-building efforts" and avoids health labour market distortions. Health workforce investments are widely recognized as essential for the achievement of global health goals, and some partners identify health workforce as a key strategic focus in their policy and strategy documents. However, most do not identify it as a key focus, and few have a published specific policy or strategy to guide health workforce investments. Several partners include optional health workforce indicators in their monitoring and evaluation processes and/or require an impact assessment for issues such as the environment and gender equality. Very few, however, have embedded efforts in their governance mechanisms to strengthen health workforce assessments. On the other hand, most have participated in health workforce information exchange activities, including strengthening information systems and health labour market analyses. Although there is evidence of participation in efforts to strengthen health workforce assessments and (especially) information exchange, the achievement of this milestone of the Global Strategy requires more structured policies for the monitoring and evaluation of health workforce investments to optimize the value of these investments and contribute towards global and national health goals.